2011
DOI: 10.1016/j.jjcc.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve for ablation of atrial fibrillation in medium-volume centers

Abstract: The time period when the procedure was performed significantly influenced the AF ablation outcome, indicating that operators in medium-volume centers should be committed to providing gratifying outcomes particularly early in the institutional experience with AF ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 27 publications
1
18
1
Order By: Relevance
“…The number of electrical cardioversions needed to treat repetitive persistent AF recurrences postablation of persistent AF was investigated. 991,992 In this small trial of 40 patients, the number of electrical cardioversions ≥3 was the only independent predictor of an ablation failure. Therefore, currently, reablation should be considered in clinical practice after two cardioversions have been performed, because of the high likelihood of recurrent arrhythmias.…”
Section: Cardioversionmentioning
confidence: 73%
See 1 more Smart Citation
“…The number of electrical cardioversions needed to treat repetitive persistent AF recurrences postablation of persistent AF was investigated. 991,992 In this small trial of 40 patients, the number of electrical cardioversions ≥3 was the only independent predictor of an ablation failure. Therefore, currently, reablation should be considered in clinical practice after two cardioversions have been performed, because of the high likelihood of recurrent arrhythmias.…”
Section: Cardioversionmentioning
confidence: 73%
“…991,992,1082,1285,1286 Exact numerical values are difficult to specify because technical skills develop at different rates. Nonetheless, comparisons of high- and low-volume centers suggest that outcomes are better at centers that have performed more than 100 procedures.…”
Section: Section 11: Training Requirementsmentioning
confidence: 99%
“…The first study that specifically addressed the importance of the learning curve during AF ablation was published by Sairaku [14] who reported on the results of the first 208 consecutive PVIs with point-by-point focal RF ablation in a mediumvolume center. A significant learning curve effect has not only been demonstrated in procedure and fluoroscopy times, but also in complication rates and in the arrhythmia-free survival at 6-month follow-up.…”
Section: Previous Studies On Learning Curve In Af Ablationmentioning
confidence: 99%
“…Efficacy and periprocedural complications are known to improve with experience in every invasive procedure including AF ablation although the learning curve effect has not been extensively evaluated. Sairaku et al [14] have reported a significantly higher incidence of procedure-related complications and a lower arrhythmia-free survival at 6-month follow-up with double Lasso catheterguided encircling PVI in the first 52 as compared with the following 156 patients who underwent the ablation. Wójcik et al [15] have demonstrated a learning curve effect with CBA as indicated by the decline in procedure and fluoroscopy times.…”
Section: Introductionmentioning
confidence: 99%
“…Current catheter ablation procedures are tedious, time-consuming, and result in significant X-ray exposure to the patient and medical team [5], [6]. Success requires highly skilled catheter manipulation in the beating heart, and constant surface contact for transmural and continuous lesions [7], [8]. …”
Section: Introductionmentioning
confidence: 99%